Quantitative Design of Bright Fluorophores and AIEgens by the Accurate Prediction of Twisted Intramolecular Charge Transfer (TICT). (3rd February 2020) - Wang, Chao; Qiao, Qinglong; Chi, Weijie; Chen, Jie; Liu, Wenjuan; Tan, Davin; McKechnie, Scott; Lyu, Da; Jiang, Xiao‐Fang; Zhou, Wei; Xu, Ning; Zhang, Qisheng; et al.
Abstract: Inhibition of TICT can significantly increase the brightness of fluorescent materials. Accurate prediction of TICT is thus critical for the quantitative design of high‐performance fluorophores and AIEgens. TICT of 14 types of popular organic fluorophores were modeled with time‐dependent density functional theory (TD‐DFT). A reliable and generalizable computational approach for modeling TICT formations was established. To demonstrate the prediction power of our approach, we quantitatively designed a boron dipyrromethene (BODIPY)‐based AIEgen which exhibits (almost) barrierless TICT rotations in monomers. Subsequent experiments validated our molecular design and showed that the aggregation of this compound turns on bright emissions with ca. 27‐fold fluorescence enhancement, as TICT formation is inhibited in molecular aggregates. Abstract : Zeitabhängige DFT‐Studien des gebogenen intramolekularen Ladungstransfers (TICT) wurden durchgeführt. Basierend auf den Berechnungen in Kombination mit experimentellen Validierungen wurden Azetidinyl‐substituierte PRODAN‐ und BODIPY‐Derivate für Anwendungen in der biologischen Bildgebung und zur aggregationsinduzierten Emission (AIE) gezielt entwickelt.